2013
DOI: 10.3390/s130709085
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Structural Health Monitoring System for the Local/Global Responses of a Large-Scale Irregular Building under Construction

Abstract: Abstract:In this study, a practical and integrative SHM system was developed and applied to a large-scale irregular building under construction, where many challenging issues exist. In the proposed sensor network, customized energy-efficient wireless sensing units (sensor nodes, repeater nodes, and master nodes) were employed and comprehensive communications from the sensor node to the remote monitoring server were conducted through wireless communications. The long-term (13-month) monitoring results recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…구조 건전도 모니터링(Structural Health Monitoring) 연 구가 활발히 진행 Park et al, 2013;Xia et al, 2014;Roussel et al, 2014)되어 왔다. 건물 에 설치된 센서로부터 계측한 응답을 이용하여 건물 내 구조 부재들의 안전성을 평가하거나 시스템 식별(system identification)을 통해 시스템 레벨의 상태를 평가한다 (Lamarche et al, 2007;Zimmerman et al, 2009;Chen et al, 2011;Ye et al, 2012).…”
Section: 서 론 건물 구조물의 상태를 파악하고 안전성을 평가하기 위한unclassified
“…구조 건전도 모니터링(Structural Health Monitoring) 연 구가 활발히 진행 Park et al, 2013;Xia et al, 2014;Roussel et al, 2014)되어 왔다. 건물 에 설치된 센서로부터 계측한 응답을 이용하여 건물 내 구조 부재들의 안전성을 평가하거나 시스템 식별(system identification)을 통해 시스템 레벨의 상태를 평가한다 (Lamarche et al, 2007;Zimmerman et al, 2009;Chen et al, 2011;Ye et al, 2012).…”
Section: 서 론 건물 구조물의 상태를 파악하고 안전성을 평가하기 위한unclassified
“…Also, it should be pointed out that in the majority of static SSI, the adopted measurements mainly contain strains or deflections whereas rotations are rarely measured. However, wide applications of inclinometers can be found in civil engineering practice, such as stadiums Design Plaza Building , high‐rise buildings, and bridges . In the study of the effect of measurement types on the estimation accuracy in a four‐node simply supported beam, it was found that the rotations were much less sensitive to errors than the vertical deflections .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, studies on the application of structural health monitoring (SHM) techniques to civil and building structures have been conducted using a variety of sensors, and the range of applications to various types of structures has increased [1–3]. …”
Section: Introductionmentioning
confidence: 99%